1995
DOI: 10.1111/j.1460-9568.1995.tb01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Achromatopsia in Monkeys

Abstract: In human cerebral achromatopsia, extrastriate cortical damage produces a severe or complete loss of colour vision, with relative sparing of non-chromatic vision. The critical lesion appears to be in a medial occipito-temporal area, occupying the lingual and caudal fusiform gyri; positron emission tomography has shown that this cortical region is one of several activated in normal human observers during colour vision tasks. Attempts to find an analogous 'colour centre' in the cortex of monkeys have not been suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 31 publications
5
49
0
Order By: Relevance
“…The percentage of color selective cells in V4 now appears little different from that in adjacent areas [48], and other investigators have emphasized its role in spatial vision [49]. Furthermore, lesions anterior and ventral to V4 in the monkey inferior temporal lobe do result in color impairments [50,51], consistent with the increased activation shown in these regions when monkeys perform color discriminations during neuroimaging [52]. Some features of the neuronal population in area V4 are consistent with a role in some aspects of color processing, notably color constancy.…”
Section: Cortical Area V4mentioning
confidence: 86%
“…The percentage of color selective cells in V4 now appears little different from that in adjacent areas [48], and other investigators have emphasized its role in spatial vision [49]. Furthermore, lesions anterior and ventral to V4 in the monkey inferior temporal lobe do result in color impairments [50,51], consistent with the increased activation shown in these regions when monkeys perform color discriminations during neuroimaging [52]. Some features of the neuronal population in area V4 are consistent with a role in some aspects of color processing, notably color constancy.…”
Section: Cortical Area V4mentioning
confidence: 86%
“…1) (Hadjikhani et al, 1998;Tootell and Hadjikhani, 2001). Furthermore, lesions including macaque TEO/TE do produce significant deficits of color vision (macaque achromatopsia) (Heywood and Cowey, 1987;Heywood et al, 1988Heywood et al, , 1992Heywood et al, , 1995. Neuroimaging (Takechi et al, 1997;Vanduffel et al, 1997;Nelissen et al, 2003) and single unit (Komatsu et al, 1992;Komatsu and Ideura, 1993;Missal et al, 1997) studies also reveal colorrelated activity in these same macaque regions.…”
Section: V4mentioning
confidence: 93%
“…In the cortex, colour information is further processed along the ventral visual pathway, through the primary visual cortex (V1) (Lennie et al, 1990;Hanazawa et al, 2000;Johnson et al, 2001;Conway et al, 2002;Solomon et al, 2004), area V2 (Gegenfurtner et al, 1996) and area V4 (Schein & Desimone, 1990;Kusunoki et al, 2006) and finally reached to the IT cortex. Lesion studies have shown that bilateral ablation of the IT cortex disrupts colour discrimination (Horel, 1994;Heywood et al, 1995;Buckley et al, 1997;Huxlin et al, 2000) although ablation of V4 does not (Heywood et al, 1992;Heywood et al, 1995), and this suggests that the IT cortex plays a key role in colour vision. Moreover, single cell recording studies have shown that there are many colour-selective neurons in the IT cortex, and that some of them have selectivities for various hues and degrees of saturation (Komatsu et al, 1992;Koida & Komatsu, 2007;Matsumora et al, 2008;Yasuda et al, 2009).…”
Section: Colour-selective Neurons In the Monkey Inferior Temporal Cortexmentioning
confidence: 99%